ANALISIS EFISIENSI TEKNIS PADA USAHA SAPI PERAH DI KECAMATAN TANJUNGSARI - Utami, Annisa Wanda; Salman, Lia Budimulyati; Firman, Achmad (Universitas Galuh Ciamis, 2020)
The dairy cow business has become a regeneration business as a family business. The dairy cow business in Indonesia is generally still a people's dairy cow business with a scale of ownership under 10 per farmer. The main problem that is still faced today is the inefficiency of farmers in the dairy business. Based on these problems, this study aims to determine the value of the technical efficiency of dairy cattle businesses, factors of production that can increase or decrease milk production, and determine the inefficiency factors in dairy cattle businesses. The study was conducted on the people's dairy cows in Tanjungsari District in August-September 2019 in the KSU area of Tandangsari. Data is collected by the survey method using a questionnaire. The analysis was performed using Frontier 4.1 software. The results of the analysis show the average value of the technical efficiency of the dairy cattle business in the study area is 0.643. The factors of production that can affect milk production are the number of lactation cows, foraging, concentrating, and labor. Factors that are thought to affect efficiency include age, experience, education, non-productive cattle, total population, main occupational dummy, and grass production, although not statistically significant. Based on the value of the technical efficiency indicates that the dairy cow business in Tanjungsari District has not been technically efficient (Et) <1 (0.643).